온프레미스-NAS 연동형 해양정보 데이터셋 공유 아키텍처 설계 및 실증 연구 - 정성훈; Seong-hoon Jeong (한국항행학회논문지, 2025)
본 연구는 해양정보와 같이 민감성과 공공성이 동시에 요구되는 데이터셋을 안전하게 저장하고 외부 활용자와 유연하게 공유할 수 있는 실용형 플랫폼으로서, 온프레미스 기반 물리적 저장 환경과 NAS (network attached storage) 기반 네트워크 공유 기능을 연동한 데이터셋 공유 아키텍처를 제안한다. 제안된 플랫폼은 Synology NAS의 QuickConnect 기술을 활용하여 고정 IP 없이도 외부사용자가 온프레미스 내 데이터에 안전하게 접근할 수 있도록 구성되었으며, DSM (disk station manager) 기반 사용자 인증, 권한 제어, 접근 로그 기록, 웹 기반 UI를 통해 보안성과 사용 편의성을 동시에 확보하였다. 제안하는 시스템은 해양수산부 ‘해양 AI (artificial intelligence) 데이터셋 hub’ 실증사업을 기반으로 총 173건의 정형 및 비정형 데이터셋을 구축하였고, 실증 테스트를 통해 응답성, 무결성, 비정형 데이터 처리 등 핵심 기능의 유효성을 검증하였다. 실증 결과, 본 플랫폼은 고가의 클라우드 인프라나 복잡한 분산 시스템 없이도 실시간 공유성과 정보 통제력을 동시에 확보할 수 있는 자립형 해양정보 인프라로서의 기술적 타당성과 정책적 활용이 가능함을 확인하였다. This study proposes a practical data-sharing platform architecture for securely storing and flexibly sharing marine datasets that require both sensitivity and public accessibility. The system integrates an on-premise physical storage environment with network attached storage based network sharing functions, enabling safe and seamless access for external users. By applying Synology NAS’s QuickConnect technology, the platform allows secure external access without the need for a static IP address. Security and usability are further enhanced through diskstation manager (DSM) based user authentication, access control, logging, and a web-based user interface. The platform was developed and verified through the Ministry of Oceans and Fisheries’ “Marine AI Dataset Hub” demonstration project, during which 173 structured and unstructured datasets were established. Validation testing confirmed the effectiveness of key functions such as response time, data integrity, and unstructured data processing. The results indicate that the proposed system can serve as a self-reliant marine data infrastructure, capable of supporting real-time sharing and governance without relying on expensive cloud infrastructure or complex distributed systems.